TEACHER CREATIVITY IN IMPLEMENTING ENJOYABLE LEARNING AT SD CILENGGANG 2 SOUTH TANGERANG CITY - may lanny, putri dwi; Andriana, Encep; Yuliana, Rina (JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
A teacher’s creativity in the learning process is one of the supporting factors. However, some teachers must be more creative and willing to develop their teaching activities. This research uses a qualitative approach and collects descriptive data through observations, interviews, and documentation. Based on the results and discussion regarding the process of teachers’ creativity in conducting attractive learning at SDN Cilenggang 2 in South Tangerang City, it concluded that teachers have been creative in implementing attractive learning. The school also supports teachers’ creativity by providing adequate learning facilities and offering teaching training to help them enhance their creativity. However, the classroom educators have not fully discovered their imagination in increasing the learning interest of 5th-grade students at SDN Cilenggang 2 in South Tangerang City. Teachers have used learning media effectively for certain subjects, although for others, they have yet to use media that aligns with the appropriate model. Due to the lack of educational games for 5th-grade students, educators still need to fully use their imagination to create an attractive teaching and learning environment. Nonetheless, teachers have created a conducive learning atmosphere by frequently conducting homerooms and encouraging students to sing to alleviate boredom during classes.